Sirtuin-dependent metabolic and epigenetic regulation of macrophages during tuberculosis - Zhang, Kangling; Sowers, Mark L.; Cherryhomes, Ellie I.; Singh, Vipul K.; Mishra, Abhishek; Restrepo, Blanca I.; Khan, Arshad; Jagannath, Chinnaswamy (Frontiers in Immunology, 2023)
Macrophages are the preeminent phagocytic cells which control multiple infections. Tuberculosis a leading cause of death in mankind and the causative organism Mycobacterium tuberculosis (Mtb) infects and persists in macrophages. Macrophages use reactive oxygen and nitrogen (ROS/RNS) and autophagy to kill and degrade microbes including Mtb. Interestingly, Glucose metabolism regulates the macrophage-mediated antimicrobial mechanisms. Whereas Glucose is essential for the growth of cells in immune cells, glucose metabolism and its down steam metabolic pathways generate key mediators which are essential co-substrates for post-translation modifications of histone proteins, which in turn, epigenetically regulate gene expression. Herein, we describe the role of Sirtuins which are NAD+-dependent histone histone/protein deacetylases during the epigenetic regulation of ROS/RNS, acetyl-CoA, NAD+ and S-adenosine methionine, and analyze the cross-talk between immunometabolism and epigenetics influencing macrophage activation and autophagy. We highlight Sirtuins as emerging therapeutic targets for modifying immunometabolism to alter macrophage phenotype and antimicrobial function.